Writing Strategies Used by Male and Female Students in Writing Their Undergraduate Theses - Shabirah, Wynneke Putri; Safitri, Dian (Universitas Negeri Padang, 2024)
This study aimed to investigate the most used writing strategies by undergraduate students that have been finished writing their thesis, the differences in strategies used across their gender, and to ascertain the extent to which these strategies impact the persistence of these students.This study was used quantitative descriptive research method to gather data through questionnaire. The participants were 44 students who have completed their theses and already had done comprehension exam in academic year 2023-2024. The data was collected by using 42-items with 4 point Likert scale questionaire adapted from Abdollahzadeh (2012) and Nopmanotham (2016) based on Oxford’s LLS (1990) Theory. The findings revealed that each participants used six writing strategies. The three types of strategies they utilize most frequently are metacognitive strategies (82%), social strategies (82%), and affective straretgies (77%) followed by compensation strategies (75%), cognitive strategies (71%) and memory strategies (71%). As can be observed, there is not much of a difference in any category’s proportion. Thefindings also revealed frequent strategies employed by male and female student was different. 21 Male students out of 44 participants (48%) reported used social strategy as most frequently and cognitive strategy as least frequently, while 23 Female students out of 44 participants (52%) reported used metacognitive strategy as the most and memory strategy as the least. The findings also revealed that students who compiled their thesis in duration one semester, two semester, three semester used metacognitive strategy as the most frequently one.This study aimed to investigate the most used writing strategies by undergraduate students that have been finished writing their thesis, the differences in strategies used across their gender, and to ascertain the extent to which these strategies impact the persistence of these students.This study was used quantitative descriptive research method to gather data through questionnaire. The participants were 44 students who have completed their theses and already had done comprehension exam in academic year 2023-2024. The data was collected by using 42-items with 4 point Likert scale questionaire adapted from Abdollahzadeh (2012) and Nopmanotham (2016) based on Oxford’s LLS (1990) Theory. The findings revealed that each participants used six writing strategies. The three types of strategies they utilize most frequently are metacognitive strategies (82%), social strategies (82%), and affective straretgies (77%) followed by compensation strategies (75%), cognitive strategies (71%) and memory strategies (71%). As can be observed, there is not much of a difference in any category’s proportion. Thefindings also revealed frequent strategies employed by male and female student was different. 21 Male students out of 44 participants (48%) reported used social strategy as most frequently and cognitive strategy as least frequently, while 23 Female students out of 44 participants (52%) reported used metacognitive strategy as the most and memory strategy as the least. The findings also revealed that students who compiled their thesis in duration one semester, two semester, three semester used metacognitive strategy as the most frequently one.